Faktor-Faktor Yang Memengaruhi Financial Performance Dengan Earning Management Sebagai Variabel Intervening - Cecilia Lisky, Sofia Prima Dewi (Jurnal Paradigma Akuntansi, 2021)
The purpose of this research is to examine the influence of independent commissioners, institutional ownership, audit quality, corporate social responsibility, and leverage toward financial performance with a mediating effect study from earning management in manufacturing companies listed in the Indonesian Stock Exchange in the period 2017-2019. The sample was determined by purposive sampling method and have 72 valid data. The research processed with path analysis using SmartPLS ver. 3.2.9. software. The result of this research shows that institutional ownership has positive effect on financial performance, while leverage has negative effect on financial performance, and independent commissioners, corporate social responsibility and earning management have no effect on financial performance. The result of this research also shows that earning management cannot mediate the influence of independent commissioners, institutional ownership, audit quality, and corporate social responsibility toward financial performance. The implication of this study is the need to increase good corporate governance, corporate social responsibility, and concern on factors in the firm that will increase the firm’s financial performance.